Pengaruh Jumlah Penyaluran Kredit Terhadap Return On Asset Pada Lembaga Keuangan Mikro Agribisnis Kabupaten Nganjuk - Indra Irianto; Muhammad Bawono (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2019)
The growth and development of LKM-A is one of the strategic steps to solve the problem of financing micro farmers and farm laborers who have been unable to obtain financial services through formal financial institutions. Empowerment which is intended, namely: (1) providing certainty of service and ease of access of farmers to financing facilities; (2) simple and fast procedures; (3) the proximity of the service location to the farmer's place of business; and (4) The A-MFI manager understands the character of farmers as customers. One of the outstanding LKM-A is Ngahuk Regency Amanah Mandiri MFI-A, because it often gets awards from the Ministry of Agriculture and Amanah-A MFI A has grown rapidly along with the large amount of credit channeled to farmers and members of cooperatives. The problems studied in writing this thesis are (1) What is the level of credit distribution seen from the position of financial statements for the period 2012, 2013, 2014, 2015, 2016. (2) What is the effect of the amount of credit distribution on Return on Assets.In writing this essay, the author uses linear regression analysis to determine the effect of independent variables on the dependent variable while the variables in this paper are Credit Distribution and Return on Assets. After the author conducted research and analysis, on the data obtained, the credit successfully channeled by the Amanah LKM-A increased in the period of 2012 to 2016. The highest credit distribution occurred in the 2016 period of Rp. 476,773,205, - and the average increase in the highest number of lending occurred in the period 2013-2014 with an increase of Rp. 144,917,263, -. Based on the results of the Simple Regression Test analysis, the value of t count <t table (-2.66 <3.18) then Ho is accepted, meaning that there is no significant effect between lending and ROA.